Eye Movement Correlates of Expertise in Visual Arts - Francuz, Piotr; Zaniewski, Iwo; Augustynowicz, Paweł; Kopiś, Natalia; Jankowski, Tomasz (Frontiers in Human Neuroscience, 2018)
The aim of this study was to search for oculomotor correlates of expertise in visual arts, in particular with regard to paintings. Achieving this goal was possible by gathering data on eye movements of two groups of participants: experts and non-experts in visual arts who viewed and appreciated the aesthetics of paintings. In particular, we were interested in whether visual arts experts more accurately recognize a balanced composition in one of the two paintings being compared simultaneously, and whether people who correctly recognize harmonious paintings are characterized by a different visual scanning strategy than those who do not recognize them. For the purposes of this study, 25 paintings with an almost ideal balanced composition have been chosen. Some of these paintings are masterpieces of the world cultural heritage, and some of them are unknown. Using Photoshop, the artist developed three additional versions of each of these paintings, differing from the original in the degree of destruction of its harmonious composition: slight, moderate, or significant. The task of the participants was to look at all versions of the same painting in pairs (including the original) and decide which of them looked more pleasing. The study involved 23 experts in art, students of art history, art education or the Academy of Fine Arts, and 19 non-experts, students in the social sciences and the humanities. The experimental manipulation of comparing pairs of paintings, whose composition is at different levels of harmony, has proved to be an effective tool for differentiating people because of their ability to distinguish paintings with balanced composition from an unbalanced one. It turned out that this ability only partly coincides with expertise understood as the effect of education in the field of visual arts. We also found that the eye movements of people who more accurately appreciated paintings with balanced composition differ from those who more liked their altered versions due to dwell time, first and average fixation duration and number of fixations. The familiarity of paintings turned out to be the factor significantly affects both the aesthetic evaluation of paintings and eye movement.